To solve the equation \(3^x = 9^x + 5\), we start by expressing \(9^x\) in terms of base \(3\):
\[ 9^x = (3^2)^x = (3^x)^2 \]
So, we can rewrite the equation as:
\[ 3^x = (3^x)^2 + 5 \]
Now, let's introduce a substitution to simplify our equation. Let \(y = 3^x\). Then we can rewrite the equation as:
\[ y = y^2 + 5 \]
Rearranging gives us a quadratic equation:
\[ y^2 - y + 5 = 0 \]
Next, we can apply the quadratic formula \(y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\). In our case, \(a = 1\), \(b = -1\), and \(c = 5\):
\[ y = \frac{-(-1) \pm \sqrt{(-1)^2 - 4 \cdot 1 \cdot 5}}{2 \cdot 1} = \frac{1 \pm \sqrt{1 - 20}}{2} \]
\[ y = \frac{1 \pm \sqrt{-19}}{2} \]
Since \(\sqrt{-19}\) is imaginary, this implies:
\[ y = \frac{1 \pm i\sqrt{19}}{2} \]
This means \(y\) (or \(3^x\)) takes complex values. Because \(3^x\) is always positive for real \(x\), there are no real solutions to the original equation \(3^x = 9^x + 5\).
Thus, the equation has no real solutions.